Packaging Differences of News Content on Title - Atiqa Sabardila; I Dewa Putu Wijana; Suhandano Suhandano (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This study investigates anything that underlie the differences of the variation on the packaging variation of the news content on the title that is based on the topicalization, the materials of news title writing, clarity and complexity of the news content, reference shifting from the title to the body of the news, roles of the mediator and the source of the news, maintaining the local value of the news, comparison between the news content on the prior text, and the ideology of the news. The analysis was conducted through pragmatic identity method, referential identity method, and traditional identity method. The data were analyzed by employing discourse approach (: micro-structure), especially the connectivity between the title to the body of the news.There are many things that underlie the differences of news content packaging on the straight news. From the structure of the news element, it can be found the several topicalizations such as the topicalization of what, who, where, when, cause, manner, or the combination of two or more elements of the news. A clear and complex package of a news content on the title gives an ease to the reader to understand the news content. However, in a package which does not put the clear reference on the title, the readers are suggested to continue to read the body of the news. Then, in a package which put the source of the news and its utterance on the title, the journalist tries to enclose the relation of the reader to the source of the news. Meanwhile, in a package which put the journalist as the mediator, the readers are invited to understand the content of the news based on their understanding and interpretation. As a commodity, any packages are utilized so that the news papers are not left behind by the readers. In a news which contains local value, the local utterances are maintained for the readers from other area to learn. Finally, in the package of the news content, the selection of the news topics becomes the ideologies which are harmonized with their vision-mission.